AN ASED MO CALCULATION OF THE ENERGY-LEVELS OF A COPPER(III) COMPLEX - THE (BIS(MALEONITRILEDITHIOLATO)COPPER(III))- COMPLEX ANION - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1991)
The molecular orbitals of bis(maleonitriledithiolato)copper(III)- were calculated by the ASED-MO method. The empty molecular orbital with 25% 3dx2-y2 (Cu) orbital character also has 41% 3s, 3p, 3d (S) and 34% 2s, 2p (C, N) atomic orbital character. Empty antibonding pi-upsilon (S) levels are below this molecular orbital. The HOMO is a pi-upsilon (S) level which has 26% 3dxz+yz character. An almost pure pi-h (S) level is below the HOMO and is followed by the b2g (pi*), pi-upsilon (S), pi-h (S), b4g (pi*), a1g (sigma*), and b3g (pi*) molecular orbitals. The sigma --> sigma* transitions from the sigma-C-s molecular orbitals to the empty molecular orbital with 25% 3dx2-y2 (Cu) atomic orbital contribution in it, which is fully allowed, is calculated to have an average oscillator strength of 1.40.
Keywords: TRANSITION-METAL SERIES; OXIDES